(untitled) (Research, Society and Development, 2021)
Introduction: The low educational level associated with low functional health literacy are major challenges for the Brazilian health system, especially primary care, as the lack of understanding of the disease will not allow the adoption of differentiated health care habits. Methods: This is an experience report carried out between January and February 2020 , following Charles Maguerez’s arch method: observation of reality - health literacy scale; key points - low health literacy, lack of user interaction with health professionals, sedentary lifestyle, low educational level and low co-responsibility with the current state of health; theorization - reading of scientific/political articles on the subject; solution hypotheses - action planning; application to reality - use of health education on diabetes. Results and Discussion: The use of learning tools and active, playful, motivating and competitive experience facilitated the teaching-learning process, promoting the dissemination of knowledge and attitudes in health among users, encouraging their self-care, and providing students with humanized training and contextualized. Conclusion: It can be concluded that these tools are applicable to different themes and can help in the health education of users of the Unified Health System, minimizing possible complications of chronic diseases, while strengthening the training of health professionals.